2014
DOI: 10.1371/journal.pone.0098052
|View full text |Cite
|
Sign up to set email alerts
|

β1,6 GlcNAc Branches-Modified PTPRT Attenuates Its Activity and Promotes Cell Migration by STAT3 Pathway

Abstract: Receptor-like protein tyrosine phosphatases (RPTPs) are type I transmembrane glycoproteins with N-glycans whose catalytic activities are regulated by dimerization. However, the intrinsic mechanism involved in dimerizing processes remains obscure. In this study, receptor protein tyrosine phosphatase rho (PTPRT) is identified as a novel substrate of N-Acetylglucosaminyltransferase V (GnT-V). We show that addition of β1,6 GlcNAc branches on PTPRT prolongs PTPRT's cell-surface retention time. GnT-V overexpression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Expression analysis of this clone further uncovered that one-third (33 out of 92) of DERE-regulated loci were transcriptionally altered ( Figure 6d and Supplementary Figure 8 ). For example, expression levels of apoptosis-related genes (for example, FOS ), transcriptional repressors (for example, SIM2 ) and tumor suppressors (for example, IFIT2 and ZIM2 ) were increased, 7 , 27 , 28 , 29 , 30 but proliferation-related loci (for example, TRAP1 and TSPAN9 ) and tyrosine kinases/phosphates (for example, ERRB4 , JAK1 and PTPRT ) were repressed, 31 , 32 , 33 , 34 , 35 confirming the anti-proliferative phenotype of DERE/del #2 cells. Ingenuity pathway analysis of these 33 genes indicated that JAK/STAT signaling participated in DERE-modulated tumor growth and deletion of this DERE region may activate MYC / FOS -involved apoptotic signaling ( Figure 6e ).…”
Section: Resultsmentioning
confidence: 99%
“…Expression analysis of this clone further uncovered that one-third (33 out of 92) of DERE-regulated loci were transcriptionally altered ( Figure 6d and Supplementary Figure 8 ). For example, expression levels of apoptosis-related genes (for example, FOS ), transcriptional repressors (for example, SIM2 ) and tumor suppressors (for example, IFIT2 and ZIM2 ) were increased, 7 , 27 , 28 , 29 , 30 but proliferation-related loci (for example, TRAP1 and TSPAN9 ) and tyrosine kinases/phosphates (for example, ERRB4 , JAK1 and PTPRT ) were repressed, 31 , 32 , 33 , 34 , 35 confirming the anti-proliferative phenotype of DERE/del #2 cells. Ingenuity pathway analysis of these 33 genes indicated that JAK/STAT signaling participated in DERE-modulated tumor growth and deletion of this DERE region may activate MYC / FOS -involved apoptotic signaling ( Figure 6e ).…”
Section: Resultsmentioning
confidence: 99%
“…Salomé et al reported that the increasing β1,6 GlcNAc branched structures could decrease bisecting GlcNAc structures on E-cadherin molecule and lead to disruption of cell-cell contacts (Pinho et al, 2009 ). Qi et al found that accumulation of this glycoform could result in enhanced cell migratory capacity by promoting PTPRT's dimerization and decreasing its catalytic activity (Qi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results using GnT-V-defective Lec4 cells transfected with GnT-V further confirmed the fact that FZD-7, when expressed in cells, is an acceptor for GnT-V. Technical difficulties, due to substantial aggregation of FZD-7 under the conditions required to release these receptors from the affinity beads before SDS-PAGE, did not allow us to resolve the 63-kDa band of FZD-7 observed without denaturation and, consequently, precluding accurate quantification of increased N-linked ␤(1,6) branching on FZD-7 after GnT-V overexpression. Many examples of glycoproteins that are cellular acceptors for GnT-V do show quantitative changes in ␤(1,6) branching when levels of GnT-V are altered; for example, integrins (12,66), cadherins (67,68), growth factor receptors (14,15,17), matriptase (69), tissue inhibitor of metalloproteinase-1 (21), and receptor-like protein tyrosine phosphatases (70). It is reasonable to conclude, therefore, that increased GnT-V expression leads to increased ␤(1,6) branching on FZD-7.…”
Section: Discussionmentioning
confidence: 99%